Management of systemic lupus erythematosus in pregnancy - Oana Denisa Bălălău; Mihai George Loghin; Delia Maria Bogheanu; Nicolae Bacalbasa; Anca Daniela Stănescu; Daniela Gabriela Bălan; Ioana Păunică; Octavian Gabriel Olaru (Journal of Mind and Medical Sciences)
Systemic lupus erythematosus is one of the most common autoimmune disorders affecting young women. Pregnant women with lupus are generally at higher risk for certain pregnancy complications than women without comorbidities. Even so, a pregnancy with lupus can be carried to term in optimal conditions if it is properly managed by a doctor. Monitoring is generally recommended six months after the onset of lupus symptoms, and ideally there should be no active lupus symptoms prior to conception. General screening tests should include the anti-phospholipid, anti-Ro and anti-La antibodies. Women who are positive for these antibodies have an increased risk of congenital heart block in the fetus. In addition, pregnant women with lupus have an increased risk of spontaneous abortion, intrauterine fetal growth restriction, pre-term birth, while neonatal lupus syndrome is a major fetal condition. The maternal risks are faced with disease flares, pre-eclampsia and other complications. Treatment options during pregnancy are limited to a few safe medications. For example, prednisone is unlikely to cause fetal malformations, but it increases the risk of diabetes and high blood pressure in the mother. Consequently, a careful multidisciplinary monitoring is essential for optimal results in pregnancy with lupus.